Demersal Fishing in Areas Beyond National Jurisdiction: A Comparative Analysis of Regional Fisheries Management Organisations - Bell, James B.; Guijarro-Garcia, Elena; Kenny, Andrew (Frontiers in Marine Science, 2019)
In areas beyond national jurisdiction, there are ten regional fisheries bodies (RFBs) responsible for the management of bottom fisheries (ABNJ). Eight of these organisations are further termed ‘Regional Fisheries Management Organisations’ (RFMOs) and have a legal mandate to regulate the sustainable use of marine living resources on the high seas. The remaining two, both in the equatorial Atlantic, are limited to advisory roles. Here we present comparisons between these organisations’ management of deep-water demersal fisheries, with particular respect to how they have respectively adopted the suite of available measures for the mitigation of significant adverse impacts (SAIs) upon vulnerable marine ecosystems (VMEs). Each organisation was scored against 99 performance criteria that either related to their capacity to implement management measures (‘Capacity’); the number and effectiveness of measures they have implemented (‘Action’); and the intensity and spatial extent of the activities they regulate (‘Need’). For most organisations, action and need scores were proportional, as the more actions an organisation takes to reduce risk to VMEs, the more it reduces the scope for improvement. However, comparisons between capacity and action scores indicate that, in some organisations, there remain several aspects of VME impact mitigation that could be improved. In the case of RFBs, or recently established RFMOs, capacity gaps are still considerable, suggesting that these organisations receive additional scientific, technical, legal, and financial support, to ensure that they are able to meet current and future objectives. Further, there is little evidence of significant cooperation between adjacent or overlapping organisations in the development and application of conservation measures, highlighting the need for an agreement on the management of biodiversity, rather than sectors, in ABNJ.